If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + 12 = -5 Reorder the terms: 12 + p = -5 Solving 12 + p = -5 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + p = -5 + -12 Combine like terms: 12 + -12 = 0 0 + p = -5 + -12 p = -5 + -12 Combine like terms: -5 + -12 = -17 p = -17 Simplifying p = -17
| 22x+3x^2=-40 | | 5x+7=5(X+2) | | (4x+9)+(3x-12)+2x=180 | | 3k-12=2k+10 | | 46x-14x^2-12=0 | | 2(q)+5(1-q)=6q+1(1-q) | | 2p-17=2(p-3)+9 | | 3x^2+22x+40=0 | | 6(5-4x)=-18 | | -7x^2+14x=x | | x(x)+4x=32 | | -3(3+5x)=96 | | 4x^2+4x+1=5 | | -7x^2+14x=y | | 0.18(y-7)+0.04y=0.12y-1.4 | | 4(p)+3(1-p)=3p+7(1-p) | | 0.5v+4.3=2.3 | | -2x-2x-5=5x-2+6 | | 3x^2+12x=y | | (x+4)=5+(5+40) | | v^2+6.1v-6=0 | | 5(4-7x)=405 | | x^2+5x=y | | 9x-4=4x-29 | | 5(p)+6(1-p)=8(p)+3(1-p) | | x-5x+5=13 | | 6(5x+9)=-96 | | 5/7=u/8 | | 25p-12= | | 5(p)+2(1-p)=4(p)+7(1-p) | | -3(y+9)=36 | | -9a^6c^4(5c^3+3a-6)= |